Cultivating the Future: A Bibliometric Review of Emerging Trends in Soilless Farming - Diego Appicciutoli; Alessandro Sebastian Amici; Deborah Bentivoglio; Giulia Chiaraluce; Giacomo Staffolani; Adele Finco (Horticulturae)
The agricultural sector faces significant challenges, including resource depletion, climate change, and a growing global population projected to reach 9 billion by 2050, requiring a 70% increase in food production. Innovative techniques like soilless farming are gaining attention as potential solutions to ensure sustainable food production. Although other bibliometric reviews have examined the possibilities of soilless farming technologies, focusing separately on certain fields such as hydroponics, aquaponics, and aeroponics, the novelty of this analysis is to provide a comprehensive view of soilless farming in the current research landscape. Using VOSviewer software (1.6.20), the study conducts a thorough analysis of 256 articles, looking at key themes, emerging trends and influential works in the field. The results showed the relevance of soilless farming and its strong link to field such as digitalization, sustainable food production, and biofortification. A strong promising area is the connection between soilless farming and urban agriculture, investigated as a theoretical tool to implement these systems in sustainable cities. The major gap emerged in the research is the lack of studies on the economic feasibility. According to the study’s findings, policymakers ought to concentrate on allocating specific funds to encourage the adoption of soilless farming, especially in urban areas.